Princely India Re-imagined A Historical Anthropology of Mysore from 1799 to the present - Ikegame, Aya (Routledge/Edinburgh South Asian Studies Series, 2013)
India's Princely States covered nearly 40 per cent of the Indian subcontinent at the time of Indian independence, and they collapsed after the departure of the British. This book provides a chronological analysis of the Princely State in colonial times and its post-colonial legacies. Focusing on one of the largest and most important of these states, the Princely State of Mysore, it offers a novel interpretation and thorough investigation of the relationship of king and subject in South Asia. The book argues that the denial of political and economic power to the king, especially after 1831 when direct British control was imposed over the state administration in Mysore, was paralleled by a counter-balancing multiplication of kingly ritual, rites, and social duties. The book looks at how, at the very time when kingly authority was lacking income and powers of patronage, its local sources of power and social roots were being reinforced and rebuilt in a variety of ways. Using a combination of historical and anthropological methodologies, and based upon substantial archival and field research, the book argues that the idea of kingship lived on in South India and continues to play a vital and important role in contemporary South Indian social and political life.